The emergence of the publicly engaged research manager. (21st February 2019) - Dunleavy, Katherine; Noble, Michael; Andrews, Heidi
Abstract : The increasing spread and rising profile of publicly engaged research in the UK has been accompanied by the emergence of a new, specialized professional services role embedded within research project teams. With this in mind, the Public Engagement Professionals in University Research Network convened a survey and workshop in 2017 to critically examine the skills and experiences of individuals in administrative roles in such projects. This paper argues that this is a highly skilled role that blurs boundaries between academic, administrator and engagement professional, but within higher education institutions it is often poorly understood and, therefore, undervalued and unsupported.